2022
DOI: 10.3390/plants12010139
|View full text |Cite
|
Sign up to set email alerts
|

Response of Cucumis sativus to Neighbors in a Species-Specific Manner

Abstract: Plants exhibit various behaviors of growth and allocation that play an important role in plant performance and social interaction as they grow together. However, it is unclear how Cucumis sativus plants respond to different neighbors. Here, we performed 5 neighbor combinations with C. sativus as the focal species. The selected materials of C. sativus responded to neighbors and exhibited different behavior strategies in a species-specific manner. All competition treatments reduced the growth of C. sativus seedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The root placement patterns of seedlings were altered and roots grew towards soybean, total root length and root dry weight in the 'Toward' region were signi cantly more than those in the 'Away' region, but not to other species, which suggested that root morphological response was not a common phenomenon. And our ndings were consistent with previous research results that the responses of plants to their neighbors were species-speci c (Ulbrich et al 2022;Zhang et al 2023).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The root placement patterns of seedlings were altered and roots grew towards soybean, total root length and root dry weight in the 'Toward' region were signi cantly more than those in the 'Away' region, but not to other species, which suggested that root morphological response was not a common phenomenon. And our ndings were consistent with previous research results that the responses of plants to their neighbors were species-speci c (Ulbrich et al 2022;Zhang et al 2023).…”
Section: Discussionsupporting
confidence: 93%
“…In order to investigate the morphological response of tomato roots to different intercropping plants, the horizontal asymmetry was calculated according to the total root length and root biomass (Zhang et al 2023). If value = 0.5 indicates no response, value > 0.5, tendency, and value < 0.5, avoidance to intercropping plant.…”
Section: Discussionmentioning
confidence: 99%
“…C. sativus emerged as the least affected species, maintaining high germination rates throughout the treatments. This resilience could be advantageous for intercropping systems, where C. sativus could be paired with crops susceptible to C. odorata's allelopathic effects to mitigate overall yield losses (Zhang, Yan and Wu, 2022). Inhibition of C. sativus when co-cultivated with neighboring plant species, such as Eruca sativa suggested a species-specific manner (Sahid and Yusoff, 2014).…”
Section: Discussionmentioning
confidence: 99%